2019
DOI: 10.1002/mp.13710
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Characterization of the new microSilicon diode detector

Abstract: PurposeDosimetric properties of the new microSilicon diode detector (60023) have been studied with focus on application in small‐field dosimetry. The influences of the dimensions of the sensitive volume and the density of the epoxy layer surrounding the silicon chip of microSilicon have been quantified and compared to its predecessor (Diode E 60017) and the microDiamond (60019, all PTW‐Freiburg, Germany).MethodsDose linearity has been studied in the range from 0.01 to 8.55 Gy and dose‐per‐pulse dependence from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 18 publications
5
34
0
Order By: Relevance
“…The choice of the reference detector influences directly the results obtained using the deconvolution method. The previous studies 12 , 13 mostly used silicon diodes as a reference, but these are subject to the density effect 15 , 27 in small fields and additionally, in larger depths or field sizes, to energy dependence. In this study, the microDiamond detector with more advantageous properties 14 , 15 , 28 has been chosen as the reference detector to train the NN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of the reference detector influences directly the results obtained using the deconvolution method. The previous studies 12 , 13 mostly used silicon diodes as a reference, but these are subject to the density effect 15 , 27 in small fields and additionally, in larger depths or field sizes, to energy dependence. In this study, the microDiamond detector with more advantageous properties 14 , 15 , 28 has been chosen as the reference detector to train the NN.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies 12 , 13 mostly used silicon diodes as a reference, but these are subject to the density effect 15 , 27 in small fields and additionally, in larger depths or field sizes, to energy dependence. In this study, the microDiamond detector with more advantageous properties 14 , 15 , 28 has been chosen as the reference detector to train the NN. In the second independent test dataset acquired at a different linear accelerator, the deconvolution results have been compared to that measured using a silicon diode due to technical incompatibilities of the microDiamond with equipment from another vendor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…126,231,232 However, the parallel irradiation of the Gafchromic™ EBT films is discouraged by Fontanarosa et al 233 who observed unacceptable under dosage in PDD at depths greater than 15 cm (about 5% at 20 cm). In general, the detectors that have smallest k f clin, f msr Q clin, Q msr factor (microdiamond, microslicon, plastic scintillator, EBT film) 78,85,97,123,156,158,[186][187][188]192,[234][235][236] are preferred to avoid the need to correct the PDD. If the institution is unable to justify acquisition of at least one of these systems, the method described by Francescon et al 237 and as described in Figure 5 could be adopted.…”
Section: Percentage Depth Dose (Pdd)mentioning
confidence: 99%
“…We also observed experimentally that the response of the 60017-type detector relative to a PTW 31010type Semiflex ionization chamber fell progressively, by up to 2%, at increasing depths in water. 10 This is most likely due to the variation of silicon diode sensitivity with dose-per-linac-pulse observed by Schönfeld et al 11 Recently, PTW-Freiburg commercialized a new "microSilicon" diode detector, the 60023-type. Some materials used in this detector have densities closer to 1 g cm -3 , and the sensitive silicon lattice has been adjusted to minimize the diode's dose-rate dependence.…”
Section: Introductionmentioning
confidence: 99%